Investigation of Structural, Electrical, and Vibrational Properties of Bi1.98A0.02Fe4O9 (A = Ba, Ce) Multiferroic Ceramics - Ashwini Kumar; Poorva Sharma; Nikhil Bhardwaj; Jingyou Tang; Guolong Tan (Advances in Materials Science and Engineering)
In this paper, we report the synthesis, phase formation, and basic characterization of polycrystalline Bi2Fe4O9, Bi1.98Ba0.02Fe4O9, and Bi1.98Ce0.02Fe4O9 samples prepared by the sol-gel technique. The crystal structure of the prepared samples has been characterized by means of X-ray diffraction and Raman scattering spectroscopy. All the obtained XRD peaks can be indexed to the orthorhombic Pbam structure and reveal the formation of Bi2Fe4O9. The Raman spectrum identifies Ag, B2g, and B3g active optical phonon modes. The crystallite size and morphology of the nanoparticles have been analyzed using scanning electron microscope (SEM). Dielectric constant (ε′) decreases as the frequency increases, and it is constant at the higher frequency region which can be explained based on the ionic conduction phenomenon in the low frequency region. The ε′ values of Bi2Fe4O9(650–850), Bi2Fe4O9(800–850), Bi1.98Ba0.02Fe4O9, and Bi1.98Ce0.02Fe4O9 samples at 10 Hz frequency are about 37, 75, 90, and 393, respectively. The observed properties signify that these materials are very useful in advanced technological and practical applications.